Local adaptations in humans - Di Rienzo, Anna (Henry Stewart Talks, 2015)
Phenotypic diversity in human populations, Selective sweeps, Clines of allele frequency, Selection on standing variation, Polygenic adaptations, Adaptive introgression, Adaptations to high altitude, Genome-wide evidence for local adaptations, Interpreting the results of selection scans, Convergent adaptations